Inovasi Pengembangan Kurikulum PAI di Sekolah Menengah Pertama Raudatut Tholabah Berbasis Pesantren - Mursalim; Hatta (Journal of Islamic Education Research, 2020)
Innovation in the development of the Islamic Education curriculum is important because of the moral decline in various elements of society. This destructive if not responded quickly, precisely, and intelligently can have a negative impact. The purpose of this study is to describe the implementation of innovative curriculum development through curricular and extracurricular activities in pesantren-based Roudhatut Thalabah Middle School. This research is a qualitative method. Data collection uses observation, interview, and documentation techniques. Data analysis uses descriptive qualitative methods. Data validity uses the triangulation of sources and techniques. The results of this study at Tholabah Middle School innovated in developing the Islamic Education curriculum through curriculum integration and collaboration between schools and dormitories. As well as making PAI subjects, in general, a nomenclature of subjects in schools, but PAI learning was developed into a stand-alone subject in the form of the Al-Qur'an, Hadis, Fiqh, SKI, and Akidah Akhlak.